Rheological Properties of Pre-treated Wastewater Treatment Plant Sludge - Yeneneh, Anteneh Mesfin; Sen, Tushar; Ang, Ha Ming; Kayaalp, A.; Kayaalp, N M. (The Australian Society of Rheology, 2014)
Sewage sludge is categorised under the class of non-Newtonian fluids and it manifests shear thinning behaviour. The flow patterns and rheology of sludge in wastewater treatment plants particularly before and after the anaerobic digestion process affects the pumping costs and the dewaterability of the digested sludge. In this study, the rheology of raw primary, thickened excess activated, mixed and digested sludge were studied for different microwave-ultrasonic pre-treatment conditions. Homogenised samples of feed , intermediate and digested sludge were subjected to rheological measurement on a HAAKE MARS Rheometer from Thermo SCIENTIFIC. The shear stress versus shear rate and viscosity versus shear rate curves were plotted for raw untreated and microwave-ultrasonic pre-treated samples at various pre-treatment conditions. The effect of solid concentration and temperature on the rheological properties of different types of sludge was also investigated. The plots were assessed as to which model they correspond or fit better, a visco-plastic model like Bingham and Herschel-Buckley model or shear thinning model like Ostwald model.The rheograms for primary, thickened excess, mixed and digested sludge samples subjected to different pre-treatment conditions were found to very different from each other. Increasing ultra-sonication time improved sludge rheology. Total solid concentration had significant impact on the viscosity and shear stress of all sludge samples. The rheology of thickened excess activated sludge at higher solid concentration is represented by the Herschel-Buckley model, which combines a power law before the sludge yields and begins to flow and the yield stress term which quantifies the amount of the stress on the sludge at the yielding point. The Bingham plastic model described well the rheology at lower solid concentration. Viscosity versus shear rate curves obeyed the power law for all sludge types considered in the study. Particle size and dewaterability progressively decreased and specific surface area increased and the rheology improved during the digestion process for all pre-treatment conditions.